LEGAL PROTECTION AGAINST THE WINNER OF THE EXECUTION OF LIABILITY RIGHTS THIRD PARTY SUBSCRIBES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This research uses Normative and enriched Empirical Juridical Methods with library and field data collection techniques which include research on legal principles, legal sources, laws and regulations, literature related to problems and interviews, are analytical descriptive and analyzing data With qualitative juridical analytical techniques and analyzes based on the Theory of Legal Protection. From the results of the study conclusions: Legal protection for auction winners against third party claims in practice has been realized in reality as contained in various preventive regulations that are repressively realized in court decisions and. Dispute resolution  is associated with resistance from third parties, the auction winner as the new owner is legal because besides being seen as a good faith party there is also a guarantee that the auction can only be canceled before the legal proceedings to control the auction object apply to the local court, namely the court in the form of emptying the auction object auction winner who has a good intention must be protected.